Trajetórias anônimas no cotidiano da cidade : a territorialização do bairro Santa Felicidade, pelos seus moradores - Shimada, Nayara Emi (2015)
This study began with the proposal to work the theme of Michel de Certeau, the study of everyday life. For this author, the everyday life goes beyond repetition and monotony; it consists of a thousand ways of doing and invents the weakest, against what is imposed to him. Because of the readings on the theme, a field of research sparked my interest, the theme of cities, and it was then that a new approach to cities in the field of organizational studies began to be understood. Therefore, I concluded that the dynamics of the city comprises more than one side, that means it can be seen through its spatial and functional organization, and also from the sight of the subjects who practice it, and own it daily. Among the reflection of these themes, there were some concepts that led me to a territorialization phenomenon. A process which concerns the way the subjects appropriate the space and become somehow attached to it, by the way that organize and give meaning to the place and / or by the built belonging effective relationships (of material possession and/or symbolic) on space, in order to establish a territory. Thus, based on these concepts, I began to investigate the history of the city of Maringá, PR, and I ended up coming across with a speech, widely reproduced by Maringá's population, of a "perfect city" with no signs of poverty or misery. However, amidst this planned reality, a particular case called my attention - the history of the Santa Felicidade neighborhood, the case that I will detail in the course of this study. Underneath this context and in the context of interventions in Maringá in favor of maintaining an urbanistic idea, I pursue to understand how the territorialization of the residents of Santa Felicidade neighborhood occurred, from the first years of foundation of the neighborhood to the present day. Thereby, with the usage of a multi-paradigmatic perspective, usage of bricolage technique, usage of oral history interviews and the adjunct of the French discourse analysis is that I could have access to practices and experiences that weave the daily lives of residents. Therefore, concerning the adversity in which they were exposed, these residents have succeeded in their everyday lives, in build their appropriations practices (material and / or symbolic) on the area throughout history. Nevertheless, the change mainly caused by the implementation of the requalification project in the neighborhood, also brought changes in the forms of appropriation of residents and consequently in the process of territorialization, that is, on how those people organized and produced meanings to that place. I came across with people who do not feel entirely belonging to the territory that they have built neither out of it. In this sense, the territorialization built is in a process of transition, where senses and meanings that were shared are being forgotten and at the same time reset, whereupon more and more the "private area" and the "individual" are being prioritized.